Affinity of new anticancer agent, 7-trimethylsilyl-ethyl-10-amino-camptothecin, to membranes and HSA determined by fluorescence spectroscopy methods - Kruszewski, Stefan; Kruszewska, Danuta M. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The application of fluorescence anisotropy measurements in determining the properties of camptothecin analogue 7-trimethylsilylethyl-10-amino-camptothecin – a promising anticancer agent – is described in this paper. The fluorescence anisotropy measurements provide useful information about binding of camptothecins to membranes and proteins, including human serum albumin (HSA). Knowledge of these properties is important for potential clinical applications of these agents, and permits to select from camptothecin analogues only those which exhibit desirable properties. An active lactone form of camptothecin in fluids at pH 7.4 hydrolyses and converts into an inactive carboxylate form. The carboxylate form of camptothecin binds easily and irreversibly to HSA. Only free carboxylate form can transform back into lactone, then in the presence of HSA one direction transition occurs (from lactone to carboxylate); therefore in HSA solution, after about two hours, the lactone form almost totaly decays. On the other hand, the camptothecins bound to membranes do not hydrolyse. Fluorescence anisotropy measurements prove that 7-trimethylsilylethyl-10-amino-camptothecin exhibits desirable properties: high affinity of its lactone form to membranes and low affinity of its carboxylate form to HSA. Such properties should ensure high stability of this drug in physiological fluids, including blood.
Optica Applicata, Vol. 38, 2008, nr 4, s. 625-633
Keywords: optyka; camptothecin; silatecan; fluorescence anisotropy; membranes binding; HSA affinity